2016
DOI: 10.4172/2167-7670.1000142
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Electric Bike Rims Coupled with Hub Motor

Abstract: In this study, static and fatigue analysis of three different electrical bikes' rim which are coupled with electrical hub motor was investigated. Loading conditions were applied on rim in order to simulate driving forces that exert on road conditions. Analysis results of three rims were compared with each other. According to results, sharp edges increase von-Mises stresses and decrease fatigue safety factor due to stress concentration on the corners. Also, it was observed that contact area of spokes to flange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Polar moment of inertia for a circular ring is calculated with: (2) where: r v -external radius, r u -internal radius.…”
Section: Verification Of the Fem Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polar moment of inertia for a circular ring is calculated with: (2) where: r v -external radius, r u -internal radius.…”
Section: Verification Of the Fem Analysis Resultsmentioning
confidence: 99%
“…Finite element method (FEM) represents a numerical method used for acquiring the relevant data of a modeled construction (displacements, stresses, vibrations, etc.). Thereby, even in the early phases of design process, possibility of obtaining reliable information about the validity of implied dimensions and correctness of estimated design solutions is enabled [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…A structural strength analysis and usage patterns for an electric bicycle frame model has been the subject of several studies. [9][10][11][12] Gorenflo et al 9 studied data collection, which included e-bike excursions and battery charging sessions over the course of roughly 3 years. Using Finite Element Analysis (FEA) simulation, the von Misses stress distribution for an electric bicycle frame with a rear battery pack component and passenger loads was presented by Cahyono et al 10 Uludamar et al 11 determined a static and fatigue analysis for three distinct electrical bike rims that are connected to an electrical hub motor.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Gorenflo et al 9 studied data collection, which included e-bike excursions and battery charging sessions over the course of roughly 3 years. Using Finite Element Analysis (FEA) simulation, the von Misses stress distribution for an electric bicycle frame with a rear battery pack component and passenger loads was presented by Cahyono et al 10 Uludamar et al 11 determined a static and fatigue analysis for three distinct electrical bike rims that are connected to an electrical hub motor. Using CATIA software and FEM analysis, Mesic et al 12 demonstrated a lightweight design concept for an electric bicycle system with front drive and an electric motor that is mounted on the bottom bracket.…”
Section: Introductionmentioning
confidence: 99%